Fractional picosecond laser-induced optical breakdown in dermatology: from controlled microinjury and molecular repair pathways to clinical endpoints and post-procedural care - Stefan Bigge; Bianca Bigge (Laser Therapy, 2026)
Fractional picosecond lasers have expanded the clinical use of ultrashort-pulse devices from tattoo and pigment removal to non-ablative rejuvenation, scar remodeling, enlarged pores, dyschromia and selected photoaging indications. Their distinctive tissue effect is not conventional fractional coagulation or ablation, but focal photomechanical disruption mediated by laser-induced optical breakdown (LIOB) and associated laser-induced cavitation (LIC), with vacuolization in epidermal and dermal tissue planes. This review synthesizes the translational evidence linking fractional optical delivery systems, histologic microinjury patterns, non-invasive imaging correlates, molecular repair pathways, clinical endpoints, safety across skin types and post-procedural care. PubMed-indexed literature was reviewed using search blocks for fractional picosecond lasers, LIOB/LIC, microlens and diffractive optical systems, optical coherence tomography (OCT), reflectance confocal microscopy (RCM), multiphoton and harmonic generation microscopy (HGM), wound healing, barrier repair, photoprotection and post-inflammatory hyperpigmentation (PIH). Current evidence shows that fractional picosecond systems can generate epidermal and dermal vacuoles, shockwave-associated optical signatures, melanin-dependent thresholds and remodeling responses involving matrix metalloproteinases (MMP), collagens, heat shock proteins (HSPs), cytokines, chemokines and barrier-related proteins. Clinical evidence is strongest for atrophic acne scars, photoaging, pores and selected non-acne scars, with increasing data in Asian and darker skin phototypes. However, the extent to which clinical outcomes are directly attributable to LIOB rather than combined photomechanical, photoacoustic and limited photothermal effects remains incompletely defined. Evidence-based aftercare remains underdeveloped. Conservative barrier support, strict photoprotection and avoidance of irritants are currently the most defensible post-procedural principles.